The large area deposition of diamond by the multi-cathode direct current plasma assisted chemical vapor deposition (DC PACVD) method - Lee, JK; Eun, KY; Baik, YJ; Cheon, HJ; Rhyu, JW; Shin, TJ; Park, JW (ELSEVIER SCIENCE SA, 2002)
Recently, considerable progress in direct current plasma assisted chemical vapor deposition (DC PACVD) of diamond materials has been achieved by adopting a multi-cathode system with cathode temperatures maintained above 2000 degreesC. This paper presents an overview of the multi-cathode DC plasma CVD method. The plasma operates in the transition region between abnormal glow and are discharges on a current-voltage curve. Its gas temperature, as estimated by optical emission spectroscopy, is approximately 3000 K. The standard apparatus composed of seven cathodes enables the deposition of diamond films with various film attributes including good optical transparency on substrates of 3-4 inches in diameter. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: MULTICATHODE